PROJETO TERAPÊUTICO SINGULAR PARA PORTADORA DE HANSENÍASE: RELATO DE EXPERIÊNCIA - Lima, Ana C. S. D.; Begnini, Danusa; Gasparini, Danieli; Flores, Andressa M.; Righi, Liane B.; Amthauer, Camila (Salão do Conhecimento, 2013)
Resumo